Factors released by low and high-LET irradiated fibroblasts modulate migration and invasiveness of pancreatic cancer cells - Charalampopoulou, Alexandra; Barcellini, Amelia; Ciocca, Mario; Di Liberto, Riccardo; Pasi, Francesca; Pullia, Marco Giuseppe; Orlandi, Ester; Facoetti, Angelica (Frontiers in Oncology, 2022)
Radiotherapy represents a major treatment option for patients with pancreatic cancer, however its benefits remain limited also due to the ability of cancer cells to migrate in the surrounding tissues. Low-LET ionizing radiation is well known to promote tumor cell migration and invasion, nevertheless little data provided by studies using high-LET radiation has led to ambiguous findings. What is hypothesized to be fundamental in the modulation of migration of tumor cells exposed to ionizing radiation is the influence of the microenvironment. Therefore, the properties of cells that populate the tumor stroma cannot be ignored when studying the influence of radiation on the migratory and invasive capacity of cancer cells. This is especially important in the case of pancreatic malignancies that are characterized by an abundance of stromal cells, including cancer-associated fibroblasts, which are known to orchestrate the cross-talk with tumor cells. The current study aims to investigate whether the presence of factors released by irradiated fibroblasts affects the migratory and invasive capacity of pancreatic cancer cells irradiated with different doses of photons or carbon ions. This challenging scenario requires a continuous and multidisciplinary approach that involves clinicians together with researcher’s expert in oncological and radiation treatment. In the last years, including preclinical experiences in a multidisciplinary approach has proved to be a winning strategy in clinical oncological research.